Territorial Anchoring in the Fringe: The Case of the Rururban Area of Bahía Blanca (Buenos Aires, Argentina) - Sereno, Claudia A. (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper describes the socio-spatial characteristics of the rururban area of Bahía Blanca. It detects the residents’ territorial anchoring to understand how it becomes a stronghold to stay there and conditions the strategies to face the urban pressures that expose them to changes and the risk of losing their property. The method builds on experiential fieldwork through observations and semi-structured interviews with locals and the thematic and contextual analyses of the data collected. The results corroborate the relationship between those residents who have robust territorial anchoring and are less willing to change and the implementation of occupancy strategies for retaining their properties and activities.